COMMUNITY EMPOWERMENT: FROM “KAMPUNG IDIOT” TO “KAMPUNG MANDIRI” (A CASE STUDY IN KARANGPATIHAN VILLAGE, PONOROGO, INDONESIA) - Rosilawati, Yeni; Amalia, Dinar Ayu; Winarsih, Atik Septi (International Journal of Psychosocial Rehabilitation, 2020)
People with intellectual disabilities in Indonesia are a group that needs support in their lives. Everyone has the right to a decent life for his or her health and well-being. Karangpatihan is a village called Kampung Idiot (Idiot Village) because 86 of its people are suffering from an intellectual disability. A community development program of self-help group (SHG) named Rumah Harapan Karangpatihan Bangkit aims to improve the social and economic capabilities of people with intellectual disabilities in Karangpatihan Village, Ponorogo, Indonesia. The researcher applied a qualitative method in the form of a case study. Data collection techniques used in this study were an in-depth interview with the Head of Karangpatihan Village, managers of Rumah Harapan Karangpatihan Bangkit, and people with intellectual disabilities involved within the program. Secondary data were obtained through the report of the SHG Rumah Harapan Karangpatihan Bangkit and mass media news clipping. The results showed that: (1) the community development program was successfully implemented through mentoring people with intellectual disabilities to various craft training activities, catfish cultivation, animal husbandry, as well as batik making; (2) the success of the program was supported by the active role of facilitators and the participation of local communities. The program was able to improve their lives and intellectual disabilities skills. Therefore, they were able to be independent, creative, have a job, and an income.